Pengaruh Kualitas Pelayanan Jasa Service Terhadap Kepuasan Konsumen Pada Dealer Yamaha Tugu Mas Bima - Abdul Latif; Intisari Haryanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The company's main product is the motorcycle, but they also offer free service, to attract buying interest. this certainly attracts consumers to buy, because consumers get a motorcycle plus get free service. of course this does not only apply to big cities, but also applies to our small cities, our waterfront cities, Kota Bima. The high expectations and the standard level of community satisfaction here, forcing motorcycle companies also need to have experts or mechanics that are reliable specifically in the service service chart. that's what faced Tugu mas Bima Dealer. In these conditions, one way to maintain competition is to improve techniques as well as possible, and also make the maximum possible performance so that customers feel happy enough and the company will survive.The purpose of this study is to find out the level of service service on Consumer Satisfaction at Yamaha Tugu Mas Bima dealers. Primary research is research used in this study. The analysis technique used is the Probability Sampling analysis technique. The sampling method used was simple random sampling with a total sample of 96 respondents. Based on the results of this study that Service Quality (X) has a significant effect on Consumer Satisfaction